Genetic architecture of various agromorphological and some quality traits in bread wheat (Triticum aestivum) - KUMAR, PRADEEP; SINGH, GYANENDRA; SINGH, DEVI; SIROHI, ANIL (The Indian Journal of Agricultural Sciences, 2016)
A study was conducted for estimating genetic parameters involving 10 parents and their 45 F1s (half diallel) of bread wheat (Triticum aestivum L.) der timely sown condition of north western plains zone of India during 2011-12 and 2012-13. Positive and significant values of F component were estimated for yield and its contributing traits in F1s indicating the preponderance of dominance and positive genes in the parents involed. The estimates of h2 were positive and significant for days to maturity (2.97), plant height (28.14), peduncle length (5.48), productive tillers (0.55), spike length (0.76), spikelets/spike (26.28), grains/spike (228.45), biological yield (149.71), grain yield (73.58), harvest index (33.15), and 1 000 grain weight (21.71). The theoretical value (0.25) of (H2/4H1) for all the traits indicated asymmetrical distribution of positive and negative genes. The proportion of dominant and recessive alleles for days to 50% flowering, days to maturity, plant height, peduncle length, productive tillers, spike length, biological yield, grain yield, harvest index and 1 000 grain weight, indicated preponderance of dominant alleles in the parents for these traits, whereas traits namely; flag leaf area, spikelets/spikes, grains/spike and gluten content, reflected more recessive alleles in the parents. Estimates of SCA effects revealed that the best cross combinations for respective traits were K 9162 × UP 2425, PBW 373 × UP 2425, K 9423 × Unnat Halna, K 9423 × HUW 560, Raj 3765 × NW 1014, K 9423 × NW 1014, NW 1014 × NW 1076, Raj 3765 × PBW, K 9423 × NW 1076, Raj 3765 × NW 1076, Raj 3765 × Unnat Halna and Unnat Halna x HUW 560 may be exploited through heterosis breeding programme to improve these traits in bread wheat. The traits showing more than 30% narrow sense heritability could be rewarding for further improvement of grain yield and gluten content in bread wheat. It may therefore be concluded that these parental lines could be used as donors for improving both the components following biparental mating or diallel selective mating system could be the best breeding methodology followed by early generation selection for improvement in these traits.